DIGITAL STRATEGIES OF EXPANDING THE SCALE OF ATTRACTION OF FOREIGN DIRECT INVESTMENTS TO THE NATIONAL ECONOMY OF UZBEKISTAN - Kamilova Iroda Khusnitdinovna (PT ANTIS International Publisher, 2024)
In alignment with the Development Strategy of New Uzbekistan for 2022-2026, enhancing the investment climate and bolstering the nation's appeal for investments is a paramount goal, with the aspiration of attracting a total of 120 billion US dollars over the next five years. This ambitious target encompasses 70 billion dollars in foreign investments and aims to concurrently boost the republic's export volume to 30 billion US dollars. Recognizing the pivotal role of digital strategies as a requisite for the rapid advancement of the national economy and the sustenance of robust economic growth, this imperative underscores the necessity to expand the scope of foreign direct investment attraction in Uzbekistan